Proceedings of the International Conference on Language, Literature, and Education (ICLLE 2018) 2018
DOI: 10.2991/iclle-18.2018.46
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Thematic Context on Contextual Learning Based on English Learning Process in the Fifth Year at As Shofa Islamic Elementary School

Abstract: This article is aimed to describe integrated thematic context on contextual learning based on English learning process in the Fifth Year of As Shofa Islamic Elementary School. The increasing in the learning quality and the learning result of the students can be interpreted and manipulated by applying the contextual learning appropriately on integrated thematic context in primary school. This integrated thematic context is applied on some English learning skills, such as listening, speaking, reading and writing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…They were aware that mastery of the English language would be beneficial for their careers, and that the gamified AR learning of English was meaningful, unlike the traditional way of learning English. The contextual learning motivated the students to link the learning material and new knowledge with real situations in the family and society [60]. This finding was consistent with Ho's study which indicated that the use of AR technology in the English class that combined learning and real-life events helped enliven the English learning experience [61].…”
Section: Connection To Real Lifesupporting
confidence: 81%
See 1 more Smart Citation
“…They were aware that mastery of the English language would be beneficial for their careers, and that the gamified AR learning of English was meaningful, unlike the traditional way of learning English. The contextual learning motivated the students to link the learning material and new knowledge with real situations in the family and society [60]. This finding was consistent with Ho's study which indicated that the use of AR technology in the English class that combined learning and real-life events helped enliven the English learning experience [61].…”
Section: Connection To Real Lifesupporting
confidence: 81%
“…Firstly, students noted that the thematic learning with specific topics helped them better understand the learning content, especially since the topics were related to daily life events and settings. In this regard the thematic learning in a real environment supported English language skills learning [60]. The data analysis also showed that integrating English skills in real-life scenes made English content more relevant and memorable, as pointed out by Liu who was of the view that thematic learning provides students with a framework to facilitate learning [62].…”
Section: Connection To Real Lifementioning
confidence: 84%
“…Community service activities which are currently reflected in the diversity of Indonesian values that are characteristic of the almighty God (Marhamah et al, 2018). In this case, Indonesian is a language that emphasizes Indonesian humanity and unity which is related to various humanitarian principles that promote social, just and prosperous souls.…”
Section: Introductionmentioning
confidence: 99%